2009
DOI: 10.1038/jid.2009.119
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of Heme Oxygenase-1 in Human Differentiated Epidermis and Its Regulation by Cytokines

Abstract: Although heme oxygenase-1 (HO-1) is induced in keratinocytes after UV radiation, HO-1 expression during normal epidermal differentiation has not yet been reported. We showed by real-time PCR, western blotting, and ELISA that HO-1 mRNA and protein expression by cultured normal human keratinocytes was upregulated during epidermal differentiation induced by a high-calcium medium. Immunohistochemical staining and in situ hybridization showed the graduated expression of HO-1 in the upper epidermis, which was accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 59 publications
7
24
1
Order By: Relevance
“…Interestingly, this study demonstrates that only NQO-1, but not HO-1 and GSTpi, is Nrf2 dependent during KC diVerentiation. Numata et al [18] also reported that the diVerentiation-dependent HO-1 expression in KC was not dependent on Nrf2, implying that the regulatory mechanism of phase 2 enzymes in relation to Nrf2 pathway might be tissue or cell speciWc. Unexpectedly, HO-1 and GSTpi were rather up-regulated in Nrf2 siRNA-transfected NHEK, implying that Nrf2 knock-down by siRNA transfection produced more stressful condition of oxidative status in NHEK, which led to the induction of Nrf2-independent enzymes (HO-1 and GSTpi) to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, this study demonstrates that only NQO-1, but not HO-1 and GSTpi, is Nrf2 dependent during KC diVerentiation. Numata et al [18] also reported that the diVerentiation-dependent HO-1 expression in KC was not dependent on Nrf2, implying that the regulatory mechanism of phase 2 enzymes in relation to Nrf2 pathway might be tissue or cell speciWc. Unexpectedly, HO-1 and GSTpi were rather up-regulated in Nrf2 siRNA-transfected NHEK, implying that Nrf2 knock-down by siRNA transfection produced more stressful condition of oxidative status in NHEK, which led to the induction of Nrf2-independent enzymes (HO-1 and GSTpi) to protect cells from oxidative stress.…”
Section: Discussionmentioning
confidence: 94%
“…When cells are exposed to stresses, then Nrf2 is translocated to the nucleus, leading to the transcriptional activation of a group of phase 2 enzyme genes such as heme oxygenase-1 (HO-1), NADP(H):quinone oxidoreductase-1 (NQO-1), and glutathione S-transferase pi (GSTpi) [11]. Interestingly, however, HO-1 was reported not to be mediated by Nrf2-transcriptional factor in diVerentiated keratinocyte (KC), implying that cell-speciWc modulation of phase 2 enzymes [18].…”
Section: Introductionmentioning
confidence: 97%
“…As keratinocytes begin to differentiate, they cease cell growth and migrate to the upper layers (the spinous, granular, and cornified layers). HO-1 is induced during the terminal differentiation and is expressed in the upper part of the epidermis (17). These layers of the skin are directly exposed to the environment and require defense mechanisms against environmental insults, including oxidative stress and ultraviolet light.…”
Section: Discussionmentioning
confidence: 99%
“…HO-1 is induced during keratinocyte differentiation and is highly expressed in the upper layers of the epidermis (17). However, the mechanism of Bach1-mediated HO-1 regulation in keratinocytes remains unclear.…”
mentioning
confidence: 99%
“…It has been shown that this enzyme can act as a powerful antioxidant (see below). We chose to follow the induction and level of this protein as a marker for the activation of the Keap1-Nrf2-ARE pathway [49]. Fig.…”
Section: Discussionmentioning
confidence: 99%